Gambaran Tingkat Kesiapsiagaan dalam Menghadapi Bencana Gempa Bumi pada Mahasiswa Fakultas Keperawatan Universitas Padjadjaran Kampus Garut - Rahmi Fitriyani; Etika Emaliyawati; Ristina Mirwanti (Universitas Padjadjaran, 2021)
Kabupaten Garut has a baribis fault, especially in the South Garut region and Mount Guntur which can cause earthquakes. Preparedness needs to be had to minimize the impact that might be caused by disaster, one of them is by students because students will be involved in all phases of the disaster. This study aims to determine the level of preparedness possessed by students of the Faculty of Nursing, Universitas Padjadjaran, Garut Campus. This research used a descriptive quantitative research design with cross sectional approach. Sampling using a total sampling technique on 356 respondents. Data collection uses a preparedness questionnaire consisting of 20 questions consisting of knowledge indicators, activity plans, disaster warning systems and resource mobilization. The data obtained were analyzed using a frequency distribution then presented in the form of a percentage. The results showed 29.8% of students were at the high level, 66.9% of students included at the moderate level, and 3.4% of students were at the low level. This study shows there are indicators of preparedness that are still lacking. Therefore, it is very important for the Garut campus to make efforts to improve student preparedness in dealing with earthquakes in the indicator of disaster warning systems